Factor using sum and product:
![Factor using sum and product class=](https://us-static.z-dn.net/files/d23/7de234a8f02a9363ddc57a32d7c665b9.png)
Answer:
[tex]x^4 - 1 = (x- 1)(x + 1)(x^2 + 1)[/tex]
[tex]2x^2 - 4x - 240 = 2(x + 10) (x - 12)[/tex]
Step-by-step explanation:
Given
[tex]1.\ x^4 - 1[/tex]
[tex]2.\ 2x^2 - 4x - 240[/tex]
Required
Factor
[tex]1.\ x^4 - 1[/tex]
Express as difference of two squares
[tex]x^4 - 1 = (x^2 - 1)(x^2 + 1)[/tex]
Express [tex]x^2 - 1[/tex] as difference of two squares
[tex]x^4 - 1 = (x- 1)(x + 1)(x^2 + 1)[/tex]
[tex]2.\ 2x^2 - 4x - 240[/tex]
Expand
[tex]2x^2 - 4x - 240 = 2x^2 -24x + 20x - 240[/tex]
Factorize
[tex]2x^2 - 4x - 240 = 2x(x -12) + 20(x - 12)[/tex]
Factor out x - 12
[tex]2x^2 - 4x - 240 = (2x + 20) (x - 12)[/tex]
Factor out 2
[tex]2x^2 - 4x - 240 = 2(x + 10) (x - 12)[/tex]